Analisis Faktor Yang Mempengaruhi Pendapatan Sektor Pariwisata Di Kota Sabang - Jalilah; Ishtafan Najmi; Ira Syariani (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The tourism sector is a sector that has the potential to be developed as a source of regional income. This is in line with what is stated in Law No. 10 of 2009 concerning tourism that the implementation of tourism is shown to increase national income in order to improve the welfare and prosperity of the people, expand and equalize business opportunities and employment opportunities, encourage regional development, introduce and utilize tourist objects and attractions. The existence of a fairly large tourism potential is expected to be a force to increase Regional Original Income, especially in the tourism sector. One area that has tourism potential is the City of Sabang which is marked by the declaration of the area as a tourist destination. The purpose of this study was to determine the effect of the number of tourists, the number of attractions, and the hotel occupancy rate on the income of the tourism sector in Sabang City. This study uses a quantitative approach through secondary data from 1999-2016. The results showed that the variables of the number of tourists, the number of attractions and the hotel occupancy rate simultaneously had a significant effect on the income of the tourism sector in Sabang City. Partially, the number of tourists has a negative and significant effect on the income of the tourism sector, the hotel occupancy rate has a positive and significant effect on the income of the tourism sector, while the tourism object variable has no significant effect on the income of the tourism sector in Sabang City.